Tropospheric Ozone Concentrations and Meteorological Parameters (Global Journal of Science Frontier Research, 2012)
In this study the Environment SA 41 m UV photometric ozone analyzer was used to determine tropospheric ozone levels. The concentrations were correlated to meteorological parameters. The daily and hourly ozone concentrations ranged between 21.07 and 50.02 ppb, and 0.08 and 96.91 respectively for Marikana; and between 4.03 and 52.04 ppb, and 6.31 and 61.76 ppb for Botsalano Game reserve. The measured hourly ozone concentrations were below the one hour ozone standard for South Africa and the World Health Organization (WHO). An 'ozone bell' behavior with daily diurnal peaking between 12:00 and 16:00 hours and a low from evening to early morning was observed; thus suggesting anthropogenic activities as a possible source of tropospheric ozone in Botsalano and Marikana. A negative correlation between ozone and relative humidity, and a positive correlation between ozone and temperature, and wind speed was also observed at the two study sites.
Keywords: ground level ozone; meteorological parameters; weekend effect; ozone bell behavior